PENGARUH KEADILAN ORGANISASI, PERSEPSI DUKUNGAN ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KONTRIBUSI KARYAWAN PENSIUN - Maya Arisandy (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2020)
This study examined the effect of effect of organization fairness, perceived  organization support and organization commitment to organizational citizenship behavior for company. The object of this research is a pension employee of PT Krakatau Steel, which is in the province of Banten, especially in Cilegon branch. 10 branches serve as a sample with 140 questionnaires distributed, but the questionnaire which can be processed as many as 100 questionnaires. Questions questionnaire measured with a scale of 1-5. Data were analyzed by using SEM (Structural Equation Model) through SmartPLS (Partial Least Square) 1:10 version. The results of this study expressed that hypotesis from organizational fairness, perceived organization support and organization commitment is positive effect and significant to organizational citizenship behaviour for company